(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper examines the manifestations of societal factions within Amish Tripathi’s Shiva Trilogy, focusing on the themes of societal strife and stagnation. By analysing the narrative elements and character interactions, this study aims to shed light on the complex dynamics of factionalism and its impact on societal progress within the trilogy. Introduction: Amish Tripathi’s Shiva Trilogy is a renowned literary work that explores the mythical world of Lord Shiva and his journey as the Neelkanth. Amidst the epic narrative, the trilogy also delves into the intricate to analyse the caste systems and demonstrate the level of depravity to which the human mind may fall in order to hang on to power and dominance. It does so by using Amish’s Shiva Trilogy as a jumping-off point. The concerns of separation and discrimination that were adhered to centuries ago and that are just as important as they were then are brought to mind by The Trilogy as a warning of the dangers of such situations. Amish investigates the myriad of restrictions that are placed on those of lower caste during the course of the Shiva Trilogy (Nagas, Vikarmas). The following are some examples of the regulations that they followed: wandering about with a drum called ‘dhol’ and pounding on it to signal their approach so that others may flee the area to avoid getting contaminated; residing outside the city borders; and not touching other people. In addition to this, it exposes the hypocrisy of Hindu philosophy and shows a community that is unable to stop allowing crime to go unpunished. The caste structures depicted in the Shiva Trilogy serve as the primary source material for the article. It is an attempt to explore their origin, nature, gravity, and deprivation, as well as to discuss how tradition and culture combine to produce a unique form of social bondage, which frequently becomes the reason for violence, physical assault, and humiliation. In addition, it is a discussion of how tradition and culture combine to produce a unique form of social bondage. In the Shiva Trilogy, the mistreatment, persecution, and caste discrimination of the Vikarmas and Nagas, as well as Shiva’s challenge to these norms, are discussed.